Osteoporosis self-assessment tool for Asians and calcaneal quantitative ultrasound for identifying primary osteoporosis in Taiwanese postmenopausal women - Liu, Dung-Huan; Lin, Chih-Sheng; Wu, Pei-Ching (Frontiers in Endocrinology, 2025)
ObjectivesThis study compares Osteoporosis Self-Assessment Tool for Asians (OSTA) and Calcaneal Quantitative Ultrasound (QUS) to detect primary osteoporosis among Taiwanese postmenopausal women and assess the consistency between both methods.Methods8,883 postmenopausal women were selected from Taiwan Biobank. Osteoporosis was diagnosed using Dual-energy X-ray absorptiometry (DXA) with T-score≦-2.5 under WHO definition. QUS and OSTA were employed to assess osteoporosis risk, with statistical analyses including receiver operating characteristic curve (ROC) analysis, Delong’s test, and McNemar’s test to compare the performance of both tools. Youden’s J statistic identifies the optimal cut-off values of OSTA and QUS SI. Cohen’s kappa coefficient (k) and Spearman’s rank correlation coefficient (rs) assessed the correlation between OSTA, QUS, and DXA.ResultsQUS outperformed OSTA with superior AUC in primary osteoporosis screening of Taiwanese postmenopausal women under WHO osteoporosis definition (AUC of QUS and OSTA are 0.737 and 0.703; p<0.05). They could independently screen and track the women at primary osteoporosis risk but not replace DXA for osteoporosis diagnosis, because they had a fair agreement of k (0.293~0.342) and a moderate correlation of rs (0.424~0.481) with DXA. They couldn’t screen and track the women at primary osteoporosis risk interchangeably because their agreement is minimal (k=0.197; rs=0.271; p<0.05).ConclusionsQUS and OSTA are radiation-free, portable, less expensive and time-consuming, and effective screening tools for primary osteoporosis in Taiwanese postmenopausal women, with QUS being the superior method under WHO osteoporosis definition. After further age-stratified analysis for detecting primary osteoporosis in Taiwanese postmenopausal women, QUS outperformed OSTA in those aged 45 - 65, while OSTA outperformed QUS in those aged 66 - 80.